Impact of Alcohol Tax Increase on Maryland College Students’ Alcohol-Related Outcomes - Smart, Mieka J. (Subst Use Misuse, 2017)
OBJECTIVE: This study A) assessed whether levels of alcohol-related disciplinary actions on college campuses changed among MD college students after the 2011 Maryland (MD) state alcohol tax increase from 6% to 9%, and B) determined which school-level factors impacted the magnitude of changes detected. METHOD: A quasi-experimental interrupted time series (ITS) analysis of panel data containing alcohol-related disciplinary actions on 33 MD college campuses in years 2006-2013. Negative binomial regression models were used to examine whether there was a statistically significant difference in counts of alcohol-related disciplinary actions comparing time before and after the tax increase. RESULTS: The ITS anaysis showed an insignificant relationship between alcohol-related disciplinary actions and tax implementation (β=−.27; p=.257) but indicated that alcohol-related disciplinary actions decreased significantly over the time under study (β=−.05; p=.022). DISCUSSION: Alcohol related disciplinary actions did decrease over time in the years of study, and this relationship was correlated with several school-level characteristics, including school price, school funding type, types of degrees awarded, and specialty. School price may serve as a proxy mediator or confounder of the effect of time on disciplinary actions.